Práticas formativas de coordenadores pedagógicos da educação infantil que são promotoras de desenvolvimento profissional - Giavoni, Regina de Fátima Arraes (2020)
The present study has the general objective of investigating whether the training practices carried out by pedagogical advisors (Educational Guidance Advisors) to pedagogical coordinators (Pedagogical Advisors) who work in early childhood education in the Municipal Education Network of Itanhaém – SP are promoters of professional development. The justification for investigating the topic through research is linked to the fact that the continuing education provided in courses, lectures and pedagogical meetings, must be planned in a qualitative way, in order to add knowledge that contributes to the professional evolution of the coordinators of the school units . Does this lead us to questions about how the annual plan for the formative actions of early childhood education in the municipality is made? What knowledge is needed for the pedagogical coordinator? How to be a transformation agent coordinator? What is the profile of the pedagogical coordinator of early childhood education? This whole issue is discussed throughout this work based on the theoretical foundation of authors who address pedagogical coordination and, above all, the role of the training coordinator. Among others, we can mention Placco, Almeida and Souza (2011), who talk about the articulating and transforming functions in the school space; Imbernón (2011) that deals with training; Tardif (2014), about the knowledge necessary for teacher coordination. Also the researches related to themes related to the pedagogical coordinator's performance as a trainer were of great value. The research methodology was developed based on the qualitative approach, with data collected in the field through official documents provided by the Education Department of Itanhaém-SP, application of questionnaires and conducting semi-structured interviews. The careful analysis of the material resulted in the creation of three categories that proved to be more relevant and are properly explained: the beginning coordinator; the formation; interpersonal / professional relationship. This work finds that even the beginning coordinators, according to themselves, are able to carry out the continuous training within their school units due to the support received; also notes that most coordinators are satisfied with the quality and with the contribution of training actions to improve their development, but there are difficulties faced by most of them in interpersonal relationships at all levels, which points to an action that can be taken. implemented to improve training practices, which is the inclusion of more themes related to interpersonal relationships in the annual framework of Early Childhood Education Actions